PROGRAM SBSN MELALUI SUBDIT SARPRAS KEMENAG RI DALAM MENINGKATKAN INFRASTRUKTUR MADRASAH - Hulu, Muhammad Arif; Arif, Mahmud; Ahmad, Ahmad (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
Madrasah is a religious-based educational institution that aims to provide religious and general knowledge. This research uses a qualitative approach with descriptive methods. The object of this research includes program implementation and its impact on madrasah facilities. Data were obtained through observation, field study, and documentation, while data analysis used data reduction, data presentation and conclusion drawing. The results show that the SBSN program for madrasah aims to improve educational facilities and infrastructure with the main requirements of legal land legality and proposal submission procedures involving documents such as land certificates, TOR, RAB, and recommendation letters from the regional Ministry of Religious Affairs. The program covers the construction of 7 types of buildings, including classrooms, laboratories, libraries, dormitories, and teachers' messes, with prototype designs that can be adapted to site conditions. The implications of this research can be used as input for related parties in improving the implementation of the SBSN program in a transparent, accountable, and sustainable manner to support the development of adequate infrastructure for madrasah education.